Natural killer T cell recognition of lipid antigens - Teyton, Luc (Biology Reports, 2009)
Natural killer T cells recognize lipid antigens in the context of CD1 molecules. Recent publications show that this mode of recognition differs substantially from that of classic T-cell receptor peptide-major histocompatibility complex interaction.